2021
DOI: 10.22541/au.163256525.58435001/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Breeding pattern of Oreochromis niloticus (Linnaeus, 1758) (Pisces: Cichlidae) versus native congeneric species, Oreochromis macrochir (Boulinger, 1912) in the upper Kabompo River, northwest of Zambia

Abstract: Investigating the determinants of reproductive biology of fishes is an essential component of biological research. Breeding pattern was investigated to determine the impact of exotic Oreochromis niloticus on the native congeneric Oreochromis macrochir in the upper Kabompo River. Gonado-somatic index and sex ratio was used to investigate the breeding pattern in both invaded (where O. niloticus is present) and uninvaded (where O. niloticus is absent) sections of the river. Oreochromis macrochir was the only nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The African sharptooth catfish was found to be the most widely distributed and this finding supports earlier observations of it being the most widely distributed fish species in Africa and it thrives in polluted water bodies (Skelton, 2001). Similar to the African sharptooth catfish, the Nile tilapia which is considered to be non‐native in most water bodies (Jere et al, 2021) was also noted to be widely distributed. Studies elsewhere indicated that the Nile tilapia has tended to dominate other species due to its aggressive ability to migrate and thrive in disturbed water habitats and its year‐round breeding patterns (Jere et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The African sharptooth catfish was found to be the most widely distributed and this finding supports earlier observations of it being the most widely distributed fish species in Africa and it thrives in polluted water bodies (Skelton, 2001). Similar to the African sharptooth catfish, the Nile tilapia which is considered to be non‐native in most water bodies (Jere et al, 2021) was also noted to be widely distributed. Studies elsewhere indicated that the Nile tilapia has tended to dominate other species due to its aggressive ability to migrate and thrive in disturbed water habitats and its year‐round breeding patterns (Jere et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Similar to the African sharptooth catfish, the Nile tilapia which is considered to be non‐native in most water bodies (Jere et al, 2021) was also noted to be widely distributed. Studies elsewhere indicated that the Nile tilapia has tended to dominate other species due to its aggressive ability to migrate and thrive in disturbed water habitats and its year‐round breeding patterns (Jere et al, 2021). The biological behaviour of the Nile tilapia could partly explain why this species was caught even in the aquaculture facilities that are not monocultures.…”
Section: Discussionmentioning
confidence: 98%